ANALYSIS OF CONCEPT UNDERSTANDING AND IMPLEMENTATION OF LEARNING THEORY OF PGSD STUDENTS OF MATARAM UNIVERSITY - Nina Sriwarthini, Ni Luh Putu; Indraswati, Dyah; Astuti, Budi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to describe the understanding of 6C PGSD students regarding learning theories and their implementation in teaching, focusing on aspects of theoretical comprehension, application, evaluation, and integration with elementary school curricula. This descriptive study involved 37 students enrolled in the Microteaching course. Data were collected through a Google Form questionnaire during November-December 2024. The results revealed that students' understanding levels were categorised as fairly good. Comprehension in the context of education reached 65%, application of theory 61%, evaluation and analysis of theory 68%, and integration of theory with elementary school curricula 64%. A portion of the students were categorised as highly proficient, particularly in the evaluation and analysis aspect (24%). However, some students still faced challenges, especially in applying theory (8%). These findings indicate that while students generally have a solid foundational understanding of learning theories, they require further reinforcement through intensive practice and applied learning approaches to enhance their implementation skills.